Está en la página 1de 16

U

U

U

U U U

U = { , ··· , } U = { , }   U =

U

=

{ , ···

, }

U = { , }

U = { , }

 

U

= {( ), ( , ), ( , , ), ( , , , ), ···}

U

U

, } U = { , }   U = { ( ) , ( ,

U = [ , +)

, ) , ( , , ) , ( , , , ) , ···} U

U

U = {(cara, ), · · · , (cara, ), (ceca, ), · · · , (ceca, )}

A = {(cara, ), (cara, ), (cara, ), (ceca, ), (ceca, ), (ceca, )}

B = {(cara, ), · · · , (cara, )}

( cara , ) , ( ceca , ) , ( ceca , ) , (

A ∪ B A B A B A ∪ B := { x ∈ U

A B A B A B

A B := {x ∈ U x A x B}.

A B = B A

,

A ∩ B A B A B A ∩ B := { x ∈ U

A B A B A B

A B := {x ∈ U x A x B}.

A B = B A

,

(A B) C = A (B C )

B := { x ∈ U x ∈ A x ∈ B } . A ∩

A B A B A ⊂ B A B A ⊂ B B ⊂ A

A B A B A B A B A B B A

A B A B A ⊂ B A B A ⊂ B B ⊂ A

  ¯ A A c A A A c := { x ∈ U x
 

¯

A A c

A

A

A c := {x ∈ U x

A}.

(A c ) c A A c = U

= A U c = c = U A A c =

x ∈ A } . ( A c ) c A ∪ A c = U

A − B A \ B A B A − B := A ∩ B

A B A\B A B

A B := A B c = {x A

x ∈ B}.
x
∈ B}.

A, B, C U

A (B C) = (A B) (A C)

A (B C) = (A B) (A C)

A = (A B) (A B)

) ∪ ( A ∩ C ) A ∪ ( B ∩ C ) = (

A, B U

(A B) c = A c B c

(A B) c = A c B c

A , B ⊂ U ( A ∪ B ) c = A c ∩ B

U U

A U A A card(A) |A|

A B

= (A B) = A + B

(A B) A B

U A A card ( A ) | A | A ∩ B = ∅ (

A, B ⊂ U

( A c ) = U − A

(A c ) = U − A

( A − B ) = A − ( A ∩ B ) ( A

(A B) = A (A B) (A B) = A + B (A B)

A c ) = U − A ( A − B ) = A − (
) = U − A ( A − B ) = A − ( A ∩

U = A A c U = A + A c

A A c

=

A = (A B) (A B)

A B = A (B A) (A B) = B + (A B) (A B) = B + A (A B)

B − A ) ( A ∪ B ) = B + ( A − B